Studi Inflectional Affixes pada Teks Naratif: Implikasinya untuk Pengajaran Bahasa Inggris - Cahyaningrum, Dewi; Wibowo, Agus Hari (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to examine the use of the inflectional affixes -es and -ed in the narrative text "The Enchanted Fish" and their implications for English language teaching. Employing a descriptive qualitative research method through content analysis, the study identifies the patterns of -es and -ed suffixes attached to verbs in the narrative text. The analysis reveals that the -es suffix represents verbs in the third-person singular form in the present tense, while the -ed suffix represents verbs in the past tense within the narrative. The findings suggest that the use of various tenses in narrative texts enhances storytelling depth and richness, aiding students in understanding contrasts between ongoing events, habitual actions or permanent states, and past occurrences. In this context, the analysis of -es and -ed inflectional affixes on verbs in narrative texts can serve as a resource for teaching students about word formation, which can then be expanded into sentence construction. Furthermore, mastering this grammatical aspect can simultaneously support students' competence in reading and writing narrative texts